Rapid optical method for procyanidins estimation in red wines. (December 2020) - Ricci, Arianna; Iaccheri, Eleonora; Benelli, Alessandro; Parpinello, Giuseppina P.; Versari, Andrea; Ragni, Luigi
Abstract: The present work outlines a reliable and rapid optical method to estimate tannin content in red wines. The method originates from the known reactivity of wine tannins (procyanidins) with proteinaceous matter (i.e. gelatin) which reaction results in a cloudiness due to the formation of floating procyanidin-protein complexes in solution. An optical device operating with a wavelength-sensitive pulsed electromagnetic source enabled to measure the extent of turbidity, combining the different intensity and spectral emission of a light source (tungsten lamp) with the photodiode wavelength sensitivity. In this experiment, 27 red wines (tannins content range: 6–1904 mg/L) were optically measured at the room temperature immediately after mixing with a saturated solution of gelatin in model wine buffer (12% ethanol, pH 3.5). An output signal waveform (voltage, V) was produced and modified as a function of peak intensity, amplitude and curvature depending on the extent of turbidity. The relationship was fitted obtaining a significant not-linear correlation (R 2 up to 0.9657) with tannins content as determined using a reference colorimetric method. The proposed new optical method is easy and cost-effective and provides a reliable alternative to the time-consuming analyses for fast in-line and off-line analysis of procyanidins in wine. Graphical abstract: Image 1 Highlights: Procyanidins evaluation in red wines has great industrial interest. An innovative optical method based on a Rapid Spectral Photometry technique was developed. Correlation between signal waveform and procyanidins content was determined. The proposed tool constitutes an economic and rapid method for quality control.